The surprising developments of digital supply chains to raise resilience in the face of disruptions - Carlos Cordon (Asian Development Bank Institute (ADBI), 2023)
We describe the need for resilience in supply chains given the recent stream of disruptions that the world has experienced. Based on recent events, we identify different types of disruptions that have challenged the resilience of supply chains. Subsequently, we describe the different digital tools used in supply chains and their success or failure in increasing the resilience of supply chains. We conclude that some digital solutions help to increase resilience, while others have almost no effect, namely systems integration, artificial intelligence (AI), and simulation. We propose a classification of how to relate the type of disruption to the effective digital tool. We finish by proposing a framework for future research to validate digital solutions that increase reliability. We also conclude that some tools, including 3D printing and blockchain, might have a role in the future in increasing the resilience of supply chains, but that today there is no evidence of a positive effect.
Keywords: M11; 330; supply chain; digital; resilience; disruptions; Industry 4.0